2004
DOI: 10.1186/1472-6963-4-24
|View full text |Cite
|
Sign up to set email alerts
|

How patient-physician encounters in critical medical situations affect trust: results of a national survey

Abstract: Background: Patients' trust in physicians and in the medical profession is vital for a successful patient-physician relationship. Trust is especially salient in critical medical situations, such as serious side-effects, hospitalizations, and diagnoses of serious medical conditions, but most trust studies have been done with the general population or in routine primary care settings. This study examines the association between patient-physician encounters in such critical medical situations and patients' trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 22 publications
3
21
1
5
Order By: Relevance
“…Values distrust was significantly higher among younger individuals and among individuals with higher household incomes. It is interesting to note that prior studies have found conflicting results about the association between income and distrust with some studies demonstrating higher levels of trust in physicians among patients with higher incomes, 58 others finding no association with income, 59 and others demonstrating higher levels of trust in patients with income <$20,000 a year as we found in this study. 23 Similarly, increasing age has been correlated with higher levels of trust in a provider 15 and with lower levels of trust in the medical profession in general.…”
Section: Discussionmentioning
confidence: 64%
“…Values distrust was significantly higher among younger individuals and among individuals with higher household incomes. It is interesting to note that prior studies have found conflicting results about the association between income and distrust with some studies demonstrating higher levels of trust in physicians among patients with higher incomes, 58 others finding no association with income, 59 and others demonstrating higher levels of trust in patients with income <$20,000 a year as we found in this study. 23 Similarly, increasing age has been correlated with higher levels of trust in a provider 15 and with lower levels of trust in the medical profession in general.…”
Section: Discussionmentioning
confidence: 64%
“…However, prior research indicates that trust in physicians is based on real health care experiences, such as past disputes, amount of contact with physicians, evaluations of the competence of physicians, and choice in selecting a physician. [27][28][29][30] Additional work is needed to examine trust among patients with other diseases. In one existing study, breast cancer patients were more trusting than other patients, perhaps due to their higher socioeconomic status relative to the other patients or to the uncertainty and risk provoked by breast cancer, which make trust especially salient and necessary for cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Pacientų pasitikėjimas gydytojais ir apskritai medicinos darbuotojais yra abipusių sėkmingų santykių prielaida (3)(4)(5)(6). Pacientų pasitikėjimas medicinos darbuotojais turi įtakos jų pasitenkinimui gydymu ir gydymo rezultatais (7).…”
Section: įVadasunclassified
“…nuo pasitikėjimo, tarpusavio pagarbos ir konfidencialumo užtikrinimo mokslinėje literatūroje skiriama pakankamai daug dėmesio. Daugumoje straipsnių konfidencialumo problema nagrinėjama pirminės sveikatos priežiūros lygmeniu (3)(4)(5)(6)(7)(8)18) ir sprendžiant problemas, susijusias su įvairiomis ligomis: psichikos, AIDS (19), užkrečiamomis ar kitomis ligomis (20), taip pat suteikiant paliatyviąją pagalbą (23). Nemažas dėmesys skiriamas paauglių problemoms (21,22).…”
Section: Pav Pacientų Ir Gydytojų Nuomonės Palyginimas Atsakant į Klunclassified